REPRESENTASI BUDAYA DALAM FOTOGRAFI MAKANAN: STUDI ANALISIS FOTO MAKAN BAJAMBA PADA KALENDER: CULTURAL REPRESENTATION IN FOOD PHOTOGRAPHY: AN ANALYSIS STUDY OF BAJAMBA FOOD PHOTOS ON CALENDARS - Pongky Purnama; Candrastuti, Ratih; Tahalea, Silviana; Novianti, Erlina (Jurnal Dimensi Seni Rupa dan Desain, 2025)
This study examines cultural representation in food photography through a visual analysis of food photographs with the theme of Makan Bajamba used in calendars. The focus of the study is directed at how visual elements, namely composition, lighting, shooting angles, colors and object arrangement, play a role in constructing cultural meaning and representing the social and ritual values ​​of the Minangkabau people, especially in Koto Gadang, West Sumatra. This study uses a qualitative approach with visual semiotic analysis methods to identify cultural signs in each photo. The results show that food photography in calendars functions not only as an aesthetic medium, but also as a representational device that emphasizes collective identity, social hierarchy, and interaction patterns in the practice of Makan Bajamba. The calendar as a distribution medium strengthens the function of photographs as reminders of cultural cycles, symbolic archivists and visual educational tools. In conclusion, the integration of food photography in calendars produces a visual narrative that combines culinary aesthetics and the rhythmic structure of tradition, thus opening up space for reinterpreting cultural practices in a contemporary context.